Lithium ion battery diaphragm slurry and lithium ion battery diaphragm

Through the cross-linking network structure of bio-based nanofibers and furylaromatic polyamide, the problem of insufficient thermal stability and puncture resistance of lithium battery separators is solved, and higher separator safety and environmental protection are achieved.

CN120357143AInactive Publication Date: 2025-07-22HEFEI ZHUOCHEN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510503921.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery separator materials have shortcomings in improving thermal stability, puncture resistance and environmental friendliness, especially the brittleness and adhesion of polymethyl methacrylate, the coating is prone to damage, and traditional materials have limitations in degradation and breathability.

Method used

The cross-linking network structure of bio-based nanofibers and furylaramide is adopted to prepare lithium-ion battery separator through electrospinning technology. The polarity of furylaramide and the cross-linking structure of bio-based nanofibers are used to improve the thermal stability and mechanical properties of the separator, and the closed-cell effect is achieved at high temperatures.

Benefits of technology

It improves the thermal stability, puncture resistance and environmental friendliness of lithium-ion battery separators, reduces the risk of environmental pollution, enhances the safety and mechanical properties of the separators, and bio-based materials can be degraded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005369225390000111
    Figure BDA0005369225390000111
Patent Text Reader

Abstract

The invention discloses lithium ion battery diaphragm slurry and a lithium ion battery diaphragm, and belongs to the technical field of lithium batteries. Furyl polyamide and bio-based nanofibers are added into the diaphragm slurry on the basis of polymethyl methacrylate; the bio-based nanofiber is a fiber with a cross-linked network structure formed by natural rubber and furyl polyamide under the cross-linking action of bismaleimide, ceramic particles in the bio-based nanofiber can be tightly embedded into the fiber, the hydrophilicity of the fiber is improved, the fiber structure is compact and stable, and the heat resistance is excellent. The raw materials for preparing the slurry are environment-friendly, the environmental pollution hazard is low, the slurry is uniform, and the synergistic effect of the materials can endow the diaphragm with better thermal stability and mechanical properties. And by utilizing the reverse reaction of a fiber cross-linked structure at high temperature, the fibers with loose structures cover the peripheral pores of the coating layer, so that high-temperature pore closing is realized, and the safety of the diaphragm is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and particularly relates to a lithium-ion battery separator slurry and a lithium-ion battery separator. Background Art

[0002] The lithium battery separator is a key component in lithium batteries. The commonly used separator material is a polyolefin film, but its performance has certain defects. Existing research mostly adds a coating on the surface of the base film to improve the performance of the separator.

[0003] Currently, the main coating materials include special alumina, boehmite, aramid, polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), etc. The inorganic materials alumina and boehmite have lower costs and can effectively improve the tensile properties and thermal stability of the separator, but have weak adhesiveness, a risk of falling off, reduced coating uniformity, and unstable battery performance; although the organic materials aramid and polyvinylidene fluoride make the separator more stable, the coating layer is more firm, and the mechanical properties and thermal stability are also improved, they are difficult to degrade, cause great environmental pollution, and have relatively poor air permeability; although polymethyl methacrylate is more environmentally friendly, it has certain brittleness itself, the coating layer is prone to damage, the puncture resistance is weak, and the heat resistance is not as good as aramid and PVDF, so there are limitations in improving the performance of the separator. Summary of the Invention

[0004] The purpose of the present invention is to provide a lithium-ion battery separator slurry and a lithium-ion battery separator, to improve the thermal stability and puncture resistance of the separator, and to improve the safety of the separator during use.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] The present invention provides a lithium-ion battery separator slurry, which, by mass parts, comprises the following raw materials:

[0007] 40 - 60 parts of polymethyl methacrylate, 15 - 25 parts of furyl aromatic polyamide, 15 - 45 parts of bio-based nanofibers, and 130 - 150 parts of a polar mixed solvent;

[0008] The bio-based nanofibers are prepared by electrospinning a spinning solution prepared by mixing furyl aromatic polyamide, natural rubber, bismaleimide, and ceramic particles, and then performing a heat cross-linking reaction;

[0009] The furyl aromatic polyamide is obtained by a polymerization reaction of a diamine monomer containing a benzene ring structure and a dicarboxylic acid containing a furan ring structure or an acyl chloride containing a furan ring structure.

[0010] Polymethyl methacrylate is water-based coating, which is more environmentally friendly than PVDF and has better adhesion, but its heat resistance is lower than that of PVDF. It is also called acrylic or plexiglass, which is a hard and brittle plastic, leading to poor interfacial performance of the separator, insufficient flexibility and puncture resistance of the coating. Cracking during the assembly process will damage the integrity of the coating and increase the risk of short circuit.

[0011] Furanyl polyamide is a bio-based material used to replace petroleum-based polyamide in current research. It has excellent comprehensive properties, including thermal stability, mechanical properties, chemical resistance and environmental friendliness. Furanyl aromatic polyamide has better heat resistance than aliphatic polyamide. And due to the presence of amide groups and furanyl groups in the structure of furanyl polyamide, it has good polarity and is soluble in polar solvents.

[0012] Further, the preparation of the furanyl aromatic polyamide is as follows: under an inert atmosphere, a diamine containing a benzene ring structure is dissolved in a polar solvent at a mass concentration of 10-30%, the temperature is controlled at -5-20°C, a diacid containing a furan ring structure or an acyl chloride containing a furan ring structure is added, and the reaction is carried out for 30-40 min. Then lithium hydroxide is added to adjust the pH to 7-8 to obtain the furanyl aromatic polyamide;

[0013] Further, the gas of the inert atmosphere is one of nitrogen, helium or argon.

[0014] Further, the diamine containing a benzene ring structure is at least one of p-phenylenediamine, m-phenylenediamine and 4,4'-diaminodiphenyl ether;

[0015] The polar solvent is one of N,N-dimethylacetamide and N-methylpyrrolidone.

[0016] Further, the diacid containing a furan ring structure is 2,5-furandicarboxylic acid;

[0017] The acyl chloride containing a furan ring structure is 2,5-furandicarbonyl chloride;

[0018] The molar ratio of the diamine containing a benzene ring structure to the diacid containing a furan ring structure or the acyl chloride containing a furan ring structure is 1:1-1.1.

[0019] Further, the preparation steps of the bio-based nanofibers are as follows:

[0020] S1. Dissolve natural rubber in an organic solvent at a concentration of 15-20 g / L. After complete dissolution, add bismaleimide, and the mass of bismaleimide is 5-10% of the mass of natural rubber. Stir evenly to form mixture A;

[0021] S2. Add ceramic particles and a polar solvent to the furanyl aromatic polyamide, mix evenly to form mixture B, and the solid content of mixture B is 15-20%.

[0022] S4. Mix mixture A and mixture B at a volume ratio of 2-4:1 to obtain mixture C, add an aqueous sodium chloride solution to increase the conductivity and form an electrospinning solution. Spin the electrospinning solution with an electrospinning device, and treat the spun fibers at 80-100 °C for 4-8 h to obtain bio-based nanofibers.

[0023] During the preparation of bio-based nanofibers, the furanyl aromatic polyamide and ceramic particles are mixed to form mixture B and then mixed with mixture A. There are polar groups in the furanyl aromatic polyamide, which can be well compatible with the ceramic particles and improve the uniformity of the inorganic materials.

[0024] Among the raw materials for the preparation of bio-based nanofibers, natural rubber can reduce carbon emissions compared with petroleum-based rubber, and generally has high elasticity and good biodegradability, but has poor heat resistance. Its structure contains double bonds and can undergo a Diels-Alder reaction with maleimide containing a conjugated π-electron system, which can improve the heat resistance of natural rubber; there are furan groups in the furanyl aromatic polyamide, which can undergo a Diels-Alder (DA) cycloaddition reaction with maleimide to form a stable six-membered ring structure. In the preparation of bio-based nanofibers, maleimide is used as a cross-linking agent to achieve a three-dimensional cross-linked network fiber structure, and the cross-linked structure is used to enhance the compactness of the fiber structure and avoid the shedding of ceramic particles, obtaining nanofibers with good heat resistance, flexibility and hydrophilicity.

[0025] Further, the organic solvent is one of tetrahydrofuran, dichloromethane and chloroform.

[0026] Further, the bismaleimide is one of N,N'-m-phenylene bismaleimide and N,N'-dithiobis(phenylmaleimide);

[0027] Further, the particle size of the ceramic particles is 50-100 nm, and the mass ratio of the ceramic particles in mixture B is 1-5%.

[0028] Further, the concentration of the aqueous sodium chloride solution is 5-10 wt%, and the volume ratio of the aqueous sodium chloride solution to mixture C is 0.5-1:10.

[0029] Further, the diameter of the bio-based nanofibers is 2-3 μm.

[0030] Further, the polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide or N-methylpyrrolidone at a volume ratio of 6-10:3.

[0031] Furthermore, the preparation steps of the lithium-ion battery separator slurry are as follows:

[0032] Polymethyl methacrylate and furan-based aromatic polyamide are added into a polar mixed solvent and mixed and stirred. After the mixture is completely dissolved, bio-based nanofibers are added and stirred evenly to obtain a lithium-ion battery separator slurry.

[0033] In the above diaphragm slurry, other raw materials are dissolved and blended with a polar mixed solvent. Bio-based nanofibers, as a material with both heat resistance and flexibility, are interlaced in the slurry to limit the crack expansion caused by stress concentration in the coating. The various polar groups in the bio-based nanofibers enable them to be evenly dispersed in the slurry. Due to the thermal reversible reaction, the cross-linked structure in the bio-based nanofibers will be decoupled at high temperatures and reduced to product molecules. At this time, the fiber structure will be loose and the volume will increase, thereby achieving coverage of the surrounding pores, achieving high-temperature closed pores, and improving the safety of the diaphragm. In addition, the diaphragm material has biodegradable properties, and the environmental pollution of post-treatment is reduced. Bio-based nanofibers are added to a mixture of polymethyl methacrylate and furan-based aromatic polyamide in the slurry. The good compatibility of bio-based nanofibers and furan-based aromatic polyamide is utilized to promote uniform mixing of materials, improve the heat resistance and mechanical properties of the diaphragm, and avoid the problem of poor dispersion of bio-based nanofibers in pure polymethyl methacrylate. Compared with pure furan-based aromatic polyamide coating, the blending of polymethyl methacrylate and furan-based aromatic polyamide can reduce cost pressure.

[0034] The present invention also provides a lithium-ion battery separator, which is prepared by coating both sides of a base film with the lithium-ion battery separator slurry described above.

[0035] Beneficial effects of the present invention:

[0036] (1) The diaphragm slurry provided by the present invention is based on polymethyl methacrylate, and furan-based polyamide and bio-based nanofibers are added. The raw materials of the slurry are environmentally friendly, the environmental pollution hazard is low, the slurry is uniform, and the diaphragm is endowed with better thermal stability and mechanical properties.

[0037] (2) The bio-based nanofibers prepared by the present invention, natural rubber and furan-based polyamide, under the cross-linking effect of bismaleimide, form fibers with a cross-linked network structure, in which the ceramic particles can be tightly embedded in the fibers to avoid falling off, the hydrophilicity of the fibers is improved, the fiber structure is compact and stable, and the heat resistance is excellent.

[0038] (3) The present invention utilizes the reverse reaction of the fiber cross-linking structure at high temperature to achieve the coverage of the pores around the coating layer by the loose structure fibers, thereby achieving high-temperature pore closure and improving the safety of the diaphragm. DETAILED DESCRIPTION

[0039] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.

[0040] Example 1

[0041] Prepare furanyl polyamide:

[0042] Under the condition of nitrogen protection, add N,N-dimethylacetamide to the reaction kettle, add 4,4'-diaminodiphenyl ether at a mass concentration of 10%, stir to dissolve, control the temperature at -5°C, add 2,5-furandicarbonyl chloride, and the molar ratio of 2,5-furandicarbonyl chloride to 4,4'-diaminodiphenyl ether is 1:1. React for 40 min, add lithium hydroxide to adjust the pH to 7-8 to obtain furanyl polyamide.

[0043] Prepare bio-based nanofibers:

[0044] S1. Dissolve natural rubber in tetrahydrofuran at a concentration of 15 g / L. After complete dissolution, add N,N'-m-phenylene bismaleimide, and the mass of N,N'-m-phenylene bismaleimide is 5% of the mass of natural rubber. Stir evenly to form mixture A;

[0045] S2. Add alumina particles with a particle size of 50-100 nm and N,N-dimethylacetamide to the furanyl aromatic polyamide, and mix evenly to form mixture B. The mass proportion of the alumina particles in mixture B is 1%, and the solid content of mixture B is 15%;

[0046] S4. Mix mixture A and mixture B in a volume ratio of 2:1 to obtain mixture C, add a sodium chloride solution with a concentration of 5 wt%, and the volume ratio of the sodium chloride solution to mixture C is 1:10 to form an electrospinning solution. Spin with an electrospinning device, and the spun fibers are treated at 100°C for 4 h to obtain bio-based nanofibers with a fiber diameter of 2-3 μm.

[0047] Prepare the slurry for lithium-ion battery separator:

[0048] This embodiment provides a slurry for a lithium-ion battery separator, which includes the following raw materials by mass parts:

[0049] 60 parts of polymethyl methacrylate, 15 parts of furanyl aromatic polyamide, 15 parts of bio-based nanofibers, and 130 parts of polar mixed solvent.

[0050] The polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide in a volume ratio of 10:3.

[0051] According to the above ratio, polymethyl methacrylate and furan-based aromatic polyamide are added to a polar mixed solvent and mixed and stirred. After complete dissolution, bio-based nanofibers are added, and after stirring evenly, a lithium-ion battery separator slurry is obtained.

[0052] Preparation of a lithium-ion battery separator:

[0053] Select a PP-based film with a thickness of 20 μm, and coat the prepared lithium-ion battery separator slurry on both sides of the base film. The coating thickness on both sides is the same. After drying to remove the solvent, a lithium-ion battery separator with a total thickness of 30 μm is obtained.

[0054] Example 2

[0055] The difference from Example 1 is only that when preparing the bio-based nanofibers, the mass ratio of alumina particles in mixture B is 3%, and other conditions and steps are the same as those in Example 1.

[0056] Example 3

[0057] The difference from Example 1 is only that when preparing the bio-based nanofibers, the mass ratio of alumina particles in mixture B is 5%, and other conditions and steps are the same as those in Example 1.

[0058] Example 4

[0059] The difference from Example 2 is only that when preparing the bio-based nanofibers, mixture A and mixture B are in a volume ratio of 3:1, and other conditions and steps are the same as those in Example 2.

[0060] Example 5

[0061] The difference from Example 2 is only that when preparing the bio-based nanofibers, mixture A and mixture B are in a volume ratio of 4:1, and other conditions and steps are the same as those in Example 2.

[0062] Example 6

[0063] The difference from Example 4 is only that when preparing the lithium-ion battery separator slurry, the raw material ratio is different. The specific ratio is as follows, and other conditions and steps are the same as those in Example 4.

[0064] This example provides a lithium-ion battery separator slurry, which includes the following raw materials by mass parts:

[0065] 50 parts of polymethyl methacrylate, 20 parts of furan-based aromatic polyamide, 30 parts of bio-based nanofibers, and 140 parts of polar mixed solvent.

[0066] The polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide in a volume ratio of 8:3.

[0067] Example 7

[0068] The only difference from Example 4 is that the ratio of raw materials is different when preparing the lithium-ion battery separator slurry. The specific ratio is as follows. Other conditions and steps are the same as Example 4.

[0069] This embodiment provides a lithium-ion battery separator slurry, which includes the following raw materials in parts by mass:

[0070] 40 parts of polymethyl methacrylate, 25 parts of furan-based aromatic polyamide, 45 parts of bio-based nanofibers, and 150 parts of polar mixed solvent.

[0071] The polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide in a volume ratio of 6:3.

[0072] Comparative Example 1

[0073] The only difference from Example 1 is that the slurry in this comparative example is directly prepared with polymethyl methacrylate.

[0074] This comparative example provides a lithium ion battery separator slurry, which includes the following raw materials in parts by mass:

[0075] 60 parts of polymethyl methacrylate, 20 parts of polyvinyl alcohol, 0.1 parts of sodium lauryl sulfate, and 130 parts of water.

[0076] According to the above proportion, polymethyl methacrylate, polyvinyl alcohol and sodium lauryl sulfate are added into water and mixed and stirred, and after stirring evenly, a lithium ion battery separator slurry is obtained.

[0077] Preparation of lithium-ion battery separators:

[0078] A PP base film with a thickness of 20 μm was selected, and the lithium ion battery separator slurry prepared above was coated on both sides of the base film. The coating thickness on both sides was the same. After drying and removing the solvent, a lithium ion battery separator with a total thickness of 30 μm was obtained.

[0079] Comparative Example 2

[0080] The only difference from Example 1 is that no bio-based nanofibers are added when preparing the lithium-ion battery separator slurry in this comparative example.

[0081] Preparation of furan-based polyamide:

[0082] Under nitrogen protection, N,N-dimethylacetamide was added to the reactor, 4,4'-diaminodiphenyl ether was added at a mass concentration of 10%, stirred and dissolved, the temperature was controlled at -5°C, 2,5-furandicarboxylic acid chloride was added, the molar ratio of 2,5-furandicarboxylic acid chloride to 4,4'-diaminodiphenyl ether was 1:1, the reaction was carried out for 40 minutes, lithium hydroxide was added to adjust the pH to 7-8, and furan-based polyamide was obtained.

[0083] Preparation of lithium-ion battery separator slurry:

[0084] This embodiment provides a lithium-ion battery separator slurry, which includes the following raw materials in parts by mass:

[0085] 60 parts of polymethyl methacrylate, 15 parts of furanyl aromatic polyamide, and 130 parts of polar mixed solvent.

[0086] The polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide in a volume ratio of 10:3.

[0087] According to the above ratio, polymethyl methacrylate and furan-based aromatic polyamide are added into a polar mixed solvent, mixed and stirred, and lithium-ion battery separator slurry is obtained after they are completely dissolved.

[0088] Preparation of lithium-ion battery separators:

[0089] A PP base film with a thickness of 20 μm was selected, and the lithium ion battery separator slurry prepared above was coated on both sides of the base film. The coating thickness on both sides was the same. After drying and removing the solvent, a lithium ion battery separator with a total thickness of 30 μm was obtained.

[0090] Comparative Example 3

[0091] The only difference from Example 1 is that in this comparative example, no furan-based aromatic polyamide is added when preparing the lithium-ion battery separator slurry.

[0092] Preparation of furan-based polyamide:

[0093] Under nitrogen protection, N,N-dimethylacetamide was added to the reactor, 4,4'-diaminodiphenyl ether was added at a mass concentration of 10%, stirred and dissolved, the temperature was controlled at -5°C, 2,5-furandicarboxylic acid chloride was added, the molar ratio of 2,5-furandicarboxylic acid chloride to 4,4'-diaminodiphenyl ether was 1:1, the reaction was carried out for 40 minutes, lithium hydroxide was added to adjust the pH to 7-8, and furan-based polyamide was obtained.

[0094] Preparation of bio-based nanofibers:

[0095] S1. Dissolve natural rubber in tetrahydrofuran at a concentration of 15 g / L. After the rubber is completely dissolved, add N,N'-m-phenylene bismaleimide, wherein the mass of the N,N'-m-phenylene bismaleimide is 5% of the mass of the natural rubber, and stir evenly to form a mixture A.

[0096] S2. Adding aluminum oxide particles with a particle size of 50-100 nm and N,N-dimethylacetamide to the furan-based aromatic polyamide, and mixing them evenly to form a mixture B, wherein the mass proportion of the aluminum oxide particles in the mixture B is 1%, and the solid content of the mixture B is 15%;

[0097] S4. Mix mixture A and mixture B in a volume ratio of 2:1 to obtain mixture C, add a sodium chloride solution with a concentration of 5 wt%, and the volume ratio of the sodium chloride solution to mixture C is 1:10 to form an electrospinning solution. Electrospin using an electrospinning device, and treat the spun fibers at 100 °C for 4 h to obtain bio-based nanofibers with a fiber diameter of 2 - 3 μm.

[0098] Prepare a lithium-ion battery separator slurry:

[0099] This example provides a lithium-ion battery separator slurry, which includes the following raw materials by mass parts:

[0100] 60 parts of polymethyl methacrylate, 15 parts of bio-based nanofibers, and 130 parts of a polar mixed solvent.

[0101] The polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide in a volume ratio of 10:3.

[0102] According to the above ratio, add polymethyl methacrylate to the polar mixed solvent, mix and stir. After complete dissolution, add bio-based nanofibers, and stir evenly to obtain a lithium-ion battery separator slurry.

[0103] Prepare a lithium-ion battery separator:

[0104] Select a PP-based film with a thickness of 20 μm, coat the prepared lithium-ion battery separator slurry on both sides of the base film, and the coating thickness on both sides is the same. After drying to remove the solvent, a lithium-ion battery separator with a total thickness of 30 μm is obtained.

[0105] Comparative Example 4

[0106] The difference from Example 1 is only that N,N'-m-phenylene bismaleimide is not added when preparing bio-based nanofibers in this comparative example.

[0107] Prepare furan-based polyamide:

[0108] Under nitrogen protection, add N,N-dimethylacetamide to a reaction kettle, add 4,4'-diaminodiphenyl ether at a mass concentration of 10%, stir to dissolve, control the temperature at -5 °C, add 2,5-furandicarbonyl chloride, and the molar ratio of 2,5-furandicarbonyl chloride to 4,4'-diaminodiphenyl ether is 1:1. React for 40 min, and add lithium hydroxide to adjust the pH to 7 - 8 to obtain furan-based polyamide.

[0109] Prepare bio-based nanofibers:

[0110] S1. Dissolve natural rubber in tetrahydrofuran at a concentration of 15 g / L, and form solution A after complete dissolution;

[0111] S2. Adding aluminum oxide particles with a particle size of 50-100 nm and N,N-dimethylacetamide to the furan-based aromatic polyamide, and mixing them evenly to form a mixture B, wherein the mass proportion of the aluminum oxide particles in the mixture B is 1%, and the solid content of the mixture B is 15%;

[0112] S4. Solution A and mixture B are mixed in a volume ratio of 2:1 to obtain mixture C, and a sodium chloride solution with a concentration of 5wt% is added, and the volume ratio of the sodium chloride solution to mixture C is 1:10 to form an electrospinning solution. The electrospinning device is used for spinning, and the fibers obtained by spinning are treated at 100°C for 4h to obtain bio-based nanofibers with a fiber diameter of 2-3μm.

[0113] Preparation of lithium-ion battery separator slurry:

[0114] This embodiment provides a lithium-ion battery separator slurry, which includes the following raw materials in parts by mass:

[0115] 60 parts of polymethyl methacrylate, 15 parts of furan-based aromatic polyamide, 15 parts of bio-based nanofibers, and 130 parts of polar mixed solvent.

[0116] The polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide in a volume ratio of 10:3.

[0117] According to the above ratio, polymethyl methacrylate and furan-based aromatic polyamide are added to a polar mixed solvent and mixed and stirred. After they are completely dissolved, bio-based nanofibers are added and stirred evenly to obtain a lithium-ion battery separator slurry.

[0118] Preparation of lithium-ion battery separators:

[0119] A PP base film with a thickness of 20 μm was selected, and the lithium ion battery separator slurry prepared above was coated on both sides of the base film. The coating thickness on both sides was the same. After drying and removing the solvent, a lithium ion battery separator with a total thickness of 30 μm was obtained.

[0120] The performance tests were performed on the diaphragms prepared in Examples 1 to 7 and Comparative Examples 1 to 4. The results are shown in Table 1:

[0121] The reference standard for thermal shrinkage and puncture strength testing is "GB / T36363-2018 Polyolefin separators for lithium-ion batteries".

[0122] Liquid absorption rate detection: Cut the prepared diaphragm into 1 cm discs, dry them in a vacuum oven, weigh them, and record them as W0. Immerse the discs in electrolyte (solute is LiPF6, solute mass fraction is 20%, solvent is EC+DMC+DEC, mass ratio is 4:2:4) for 12 hours, absorb the residual liquid on the surface with filter paper, weigh and record them as W1. Liquid absorption rate = (W1-W0)W0×100%.

[0123] The prepared separator was cut into a circular shape with a diameter of 18 mm and assembled into a button cell, and the EIS test method of an electrochemical workstation was adopted.

[0124] Table 1

[0125]

[0126] It can be seen from Table 1 that with the increase of alumina particles in the bio-based nanofibers, the thermal stability and liquid absorption rate of the separator prepared after slurry coating are both improved. However, excessive alumina will damage the flexibility of the fibers, the effect of reducing crack propagation is weakened, and the puncture strength of the separator is reduced. When adjusting the ratio of natural rubber and furanyl aromatic polyamide in the bio-based nanofibers, at the ratio of Example 4, the cross-linked structure of the materials in the fiber structure is the best, and its effect on improving the puncture strength of the separator is significant. In Examples 6 and 7, with the increase of the ratio of furanyl aromatic polyamide and bio-based nanofibers, the mechanical properties and thermal stability of the separator coated with slurry are both improved. It can be seen from Example 1 and Comparative Example 1 that in the prior art, when the coating slurry prepared with polymethyl methacrylate does not add the bio-based nanofibers and furanyl aromatic polyamide provided by the present invention, the performance indexes of the prepared separator are poor; combining Example 1, Comparative Example 1 and Comparative Example 2, it can be known that under the condition of only not adding bio-based nanofibers, the puncture resistance and thermal stability of the separator are significantly lower than those of Example 1. However, adding furanyl aromatic polyamide to the slurry has a certain promoting effect on the performance of the separator, and the performance is better than that of Comparative Example 1; in Comparative Example 3, although bio-based nanofibers are added, in the absence of furanyl aromatic polyamide, the compatibility between the fibers and polymethyl methacrylate is poor, and the interfacial bonding force is weak, resulting in a decrease in the effect of bio-based nanofibers on improving the performance of the separator. In Comparative Example 4, without adding a cross-linking agent, the structure of the prepared bio-based nanofibers is loose, and the alumina particles therein cannot be tightly embedded, and the fracture probability increases during fiber preparation. Compared with Example 1, the mechanical properties of the separator decrease significantly. Combining Comparative Example 4 and Example 1, it can be known that in the absence of cross-linking reaction of the fibers, the reverse reaction at high temperature cannot proceed, and when the thermal closing effect does not exist, the micropores of the coating layer cannot be covered and closed after heating, the impedance does not change significantly, and the safety risk of the separator increases.

[0127] It should be noted that in this text, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements not only includes those elements, but also includes other elements not expressly listed, or elements inherent to such process, method, article or device.

[0128] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lithium-ion battery separator slurry, characterized in that, By mass parts, it includes the following raw materials: 40 - 60 parts of polymethyl methacrylate, 15 - 25 parts of furan-based aromatic polyamide, 15 - 45 parts of bio-based nanofibers, 130 - 150 parts of polar mixed solvent; The bio-based nanofibers are prepared by electrospinning a spinning solution prepared by mixing furan-based aromatic polyamide, natural rubber, bismaleimide and ceramic particles, and then performing a heat cross-linking reaction; The furan-based aromatic polyamide is obtained by a polymerization reaction of a diamine monomer containing a benzene ring structure and a dicarboxylic acid containing a furan ring structure or an acyl chloride containing a furan ring structure.

2. The lithium-ion battery separator slurry according to claim 1, wherein The preparation of the furan-based aromatic polyamide is as follows: Under an inert atmosphere, a diamine containing a benzene ring structure is dissolved in a polar solvent at a mass concentration of 10 - 30%, the temperature is controlled at -5 - 20 °C, a dicarboxylic acid containing a furan ring structure or an acyl chloride containing a furan ring structure is added, and the reaction is carried out for 30 - 40 min. Then lithium hydroxide is added to adjust the pH to 7 - 8 to obtain the furan-based aromatic polyamide.

3. The lithium-ion battery separator slurry according to claim 2, characterized in that, The diamine containing a benzene ring structure is at least one of p-phenylenediamine, m-phenylenediamine and 4,4'-diaminodiphenyl ether; The polar solvent is one of N,N-dimethylacetamide and N-methylpyrrolidone; The dicarboxylic acid containing a furan ring structure is 2,5-furandicarboxylic acid; The acyl chloride containing a furan ring structure is 2,5-furandicarbonyl chloride; The molar ratio of the diamine containing a benzene ring structure to the dicarboxylic acid containing a furan ring structure or the acyl chloride containing a furan ring structure is 1:1 - 1.

1.

4. A lithium-ion battery separator slurry according to claim 1, characterized in that, The preparation steps of the bio-based nanofibers are as follows: S1. Dissolve natural rubber in an organic solvent at a concentration of 15 - 20 g / L. After complete dissolution, add bismaleimide, and the mass of bismaleimide is 5 - 10% of the mass of natural rubber. Stir evenly to form mixture A; S2. Add ceramic particles and a polar solvent to the furan-based aromatic polyamide, and mix evenly to form mixture B. The solid content of mixture B is 15 - 20%; S4. Mix mixture A and mixture B at a volume ratio of 2 - 4:1 to obtain mixture C. Add an aqueous sodium chloride solution to increase the conductivity to form an electrospinning solution. Electrospin with an electrospinning device, and treat the spun fibers at 80 - 120 °C for 2 - 4 h to obtain bio-based nanofibers.

5. A lithium-ion battery separator slurry according to claim 4, characterized in that, The bismaleimide is one of N,N'-m-phenylene bismaleimide and N,N'-dithiobis(phenylmaleimide); 6. The lithium-ion battery separator slurry according to claim 4, characterized in that, The particle size of the ceramic particles is 50 - 100 nm, and the mass proportion of the ceramic particles in mixture B is 1 - 5%; 7. A lithium-ion battery separator slurry according to claim 1, wherein The diameter of the bio-based nanofibers is 2 - 3 μm; 8. The lithium-ion battery separator slurry according to claim 1, wherein The polar mixed solvent is obtained by mixing acetone and N,N-dimethylacetamide or N-methylpyrrolidone at a volume ratio of 6 - 10:3; 9. The lithium ion battery separator slurry according to claim 1, characterized in that, The preparation steps of the lithium-ion battery separator slurry are as follows: Add polymethyl methacrylate and furan-based aromatic polyamide to a polar mixed solvent, mix and stir. After complete dissolution, add bio-based nanofibers and stir evenly to obtain the lithium-ion battery separator slurry.

10. A lithium-ion battery separator, characterized in that, The lithium-ion battery separator is prepared by coating both sides of a base film with a lithium-ion battery separator slurry as described in any one of claims 1-9.

Citation Information

Cited By

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN121192375A